2015
DOI: 10.1108/pijpsm-12-2014-0136
|View full text |Cite
|
Sign up to set email alerts
|

Critical moments in police-citizen reconciliation

Abstract: Purpose -The purpose of this paper is to analyze the interaction of police and citizen representatives during critical moments in reconciliation processes through a relational model. Design/methodology/approach -Based on 26 in-depth interviews with key actors in three different cases of media-salient police-citizen group conflict, the interactions in the run-up to, during and after five moments that were critical in the transformation from conflict to cooperation, were analyzed. In focussing on the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…While the presence of vicarious trauma cannot be readily reversed, the relationship between the police and African Americans can be improved (O’Brien et al, 2020). Police need to hear the concerns of the Black community, and vice versa, and trust may be rebuilt between both sides through reconciliation (Stronks & Adang, 2015). One of the major contributions of the current study is that it employed a sample of adults who live in public housing, middle-income, and upper-middle-income communities.…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of vicarious trauma cannot be readily reversed, the relationship between the police and African Americans can be improved (O’Brien et al, 2020). Police need to hear the concerns of the Black community, and vice versa, and trust may be rebuilt between both sides through reconciliation (Stronks & Adang, 2015). One of the major contributions of the current study is that it employed a sample of adults who live in public housing, middle-income, and upper-middle-income communities.…”
Section: Discussionmentioning
confidence: 99%
“…Het begrip 'relatieveiligheid', ten tweede, refereert aan de voorspelbaarheid van de interacties tussen partijen en aan het vertrouwen dat het gedrag van de andere partij niet van het ene op het andere moment in negatieve zin omslaat. Zeker in de context van gewelddadig conflict spelen percepties van de relatieveiligheid vaak een belangrijke rol: conflicten leveren spanning en stress op, die maken dat je gaat twijfelen aan de relatieveiligheid (Stronks & Adang, 2015). De 'relatiecompatibiliteit', tot slot, refereert aan de aard van de betrokken partijen (wordt een partij gezien als van nature coöperatiever, vermijdend, confronterend?)…”
Section: 1unclassified
“…Relatiecompatibiliteit gaat daarnaast, zo stelt Stronks (2017) vast, ook over de mate van sociale identificatie met de ander, in de zin dat partijen al dan niet worden gezien als onderdeel van dezelfde sociale groep, met dezelfde kenmerken, normen en waarden, doelen en belangen (Tajfel & Turner, 1976). Als mensen zich sociaal meer identificeren met anderen zijn zij eerder bereid om samen te werken, toenadering te zoeken, te onderhandelen en energie te steken in coöperatief contact (Tajfel & Turner, 1976;Stronks & Adang, 2015). Tabel 1 vat het bovenstaande samen en geeft de relatiekwaliteiten en de deelaspecten daarvan weer zoals we deze in dit onderzoek onderscheiden.…”
Section: 1unclassified
“…Further, several studies have shown a strong correlation between officer age and experience and poor conflict management behavior, with complaints being more frequent for inexperienced officers, with a steady decline with experience (Terrill & Ingram, 2015). Other studies have focused on conflict management tools for the police to improve strained relations between the police and members of the public, including the role of mediation and reconciliation processes (Berger, 2000;Stronks & Adang, 2015;van de Klomp et al, 2014). Further, a study from Hong Kong examined the effectiveness of conflict-management training for traffic police officers and highlighted three major components -heightening awareness of emotional reaction and conflict-management approaches, improving communication skills, and enhancing anger management and emotional regulation -that can be utilized in law enforcement operations (Lau et al, 2004).…”
Section: Previous Researchmentioning
confidence: 99%